Determination of antifungal volatile organic compounds of upland rice vinegar and their inhibition effects on Aspergillus flavus in dried chili pepper. (April 2022) - Pothimon, Ruttipron; Krusong, Warawut; Daetae, Pawinee; Tantratian, Sumate; Gullo, Maria
Abstract: Determination of volatile organic components (VOC) produced in high acid upland rice vinegar was conducted using GC-MS. Acetic acid and ethyl acetate at 9.11% and 2.69% (v/v), respectively, were major VOC found in the vinegar while the others were isobutyl acetate, isobutyl alcohol, isoamyl acetate, isoamyl alcohol, phenethyl acetate and phenethyl alcohol. Subsequently, vinegar and VOC were tested, in vitro, for their inhibition on conidia germination of 10 3 conidia/mL of Aspergillus flavus . The exposure with 10% (v/v) of vapor-phase vinegar and pure acetic acid completely inhibited the germination of conidia with 30 min exposure, while VOC mixture of 9.11% (v/v) acetic acid, 0.08% (v/v) isoamyl alcohol, 0.45% (v/v) phenethyl alcohol and 0.01% (v/v) isobutyl alcohol with 45 min exposure could achieve the same target. Then, vinegar vapor was tested on the inhibition of conidia germination and aflatoxin production of A. flavus during 90 d subsequent storage of dried chili pepper. Complete inhibition of conidia germination and aflatoxin production were achieved with the 40 min exposure of 1.04 ± 0.03 mmol/L of vaporized vinegar. Our results showed that fumigation of upland rice vinegar containing antifungal VOC is a simple and an economical method for commercial preservation of dried chili pepper. Upland rice vinegar is a novel bio-fumigant for prevention of mycotoxin production in dried food and feed products during storage. Graphical abstract: Image 1 Highlights: Dried chili pepper can be contaminated with Aspergillus flavus resulting in high level of aflatoxin. . Volatile organic compounds can enhance the antifungal activity of upland rice vinegar. Upland rice vinegar and its volatile organic compounds can inhibit the conidia germination of Aspergillus flavus. No aflatoxin in dried chili pepper is found during 90 d storage after vapor treatment by upland rice vinegar. Upland rice vinegar is a novel bio-fumigant which have high antifungal activity.